História natural, morfometria e atributos funcionais das aranhas cavernícolas brasileiras das famílias Telemidae Fage, 1913 e Ochyroceratidae Fage, 1912 (Araneomorphae) - Duarte, Marcus Vinícius da Silva Agua (Universidade Federal de São Carlos, 2026)
Subterranean ecosystems constitute highly selective environments, acting as strong environmental filters due to energetic limitation, low food availability, and reduced carrying capacity. Despite these constraints, such environments harbor a singular biodiversity, characterized by high levels of endemism and by highly specialized organisms exhibiting morphological, physiological, and behavioral traits associated with life under permanent darkness and microclimatic stability. Among subterranean arthropods, spiders stand out as one of the richest and most abundant groups, with particular representation of the families Telemidae and Ochyroceratidae in caves of the world. However, most studies on these groups have been predominantly taxonomic and descriptive, with a notable lack of research addressing ecological aspects, population structure, and functional attributes, which are essential for understanding evolutionary processes and for guiding conservation strategies. This dissertation aimed to investigate the geographic distribution, morphological variation, and functional attributes of Neotropical cave-dwelling spiders of the families Telemidae and Ochyroceratidae, with emphasis on the genus Pinelema and the troglobitic species Pinelema elinae. To achieve this, an integrative approach was employed, combining natural history data, potential distribution modeling based on maximum entropy, linear and geometric morphometric analyses, and comparative assessments of functional trait diversity among troglobitic, troglophilic, and epigean species. The results of the potential distribution modeling indicated that the occurrence of the genus Pinelema, and particularly P. elinae, is strongly influenced by climatic variables associated with thermal and hydric stability, especially temperature seasonality and precipitation-related variables. Paleoclimatic projections suggested a fragmented potential distribution during the Last Glacial Maximum and the Holocene, supporting hypotheses of historical isolation and high vulnerability of subterranean populations. Spatial analyses further revealed that a large proportion of areas with high environmental suitability is currently under intense anthropogenic pressure, often lying outside formally protected areas. Morphometric analyses of Pinelema elinae populations from the Serra do Ramalho revealed significant sexual dimorphism and marked morphological differences among populations, suggesting differentiation processes associated with isolation among caves. Functional trait diversity analyses revealed contrasting patterns among the ecological–evolutionary categories examined. Troglobitic morphospecies exhibited the highest functional diversity values and a consistent tendency toward functional overdispersion relative to null models, indicating high trait heterogeneity and strong differentiation within the multivariate functional space. This pattern suggests the influence of niche partitioning processes, potentially associated with specialization in microhabitats and differential resource use in subterranean environments. Troglophilic morphospecies showed intermediate functional diversity values without significant deviations from random expectations, whereas epigean morphospecies displayed lower functional diversity and trait clustering, reflecting the predominance of environmental filtering imposed by surface conditions. Overall, the results demonstrate that the distribution, morphology, and functional attributes of the studied spiders are shaped by a combination of environmental, historical, and evolutionary factors, reinforcing the role of subterranean isolation as a driver of biological differentiation and highlighting the importance of conserving Neotropical cave ecosystems.
Natural history, morphometry and functional attributes of Brazilian cave-dwelling spiders of the families Telemidae Fage, 1913 and Ochyroceratidae Fage, 1912 (Araneomorphae)
Keywords: Ecologia; Distribuição Potencial; Morfometria Linear; Morfometria Geométrica; Diversidade Funcional; CIENCIAS BIOLOGICAS::ECOLOGIA::ECOLOGIA APLICADA; 15. Vida Terrestre